2001
DOI: 10.1084/jem.194.9.1219
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin Is Involved in the Initiation of Cutaneous Contact Hypersensitivity by Inducing Langerhans and Dendritic Cell Migration to Lymph Nodes

Abstract: Osteopontin (OPN) is a chemotactic protein that attracts immune cells, to inflammatory sites. The sensitization phase of allergic cutaneous contact hypersensitivity (CHS) requires the migration of Langerhans cells/dendritic cells (LCs/DCs) from skin to draining lymph nodes. Characterizing OPN function for LC/DC migration we found upregulated OPN expression in hapten sensitized skin and draining lymph nodes. OPN induces chemotactic LC/DC migration, initiates their emigration from the epidermis, and attracts LCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
136
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(142 citation statements)
references
References 45 publications
5
136
0
1
Order By: Relevance
“…4.3). It has been reported that OPN deficiency reduces the recruitment of macrophages, neutrophils and dendritic cells Koh et al, 2007;Weiss et al, 2001). These results imply that OPN allows the expression of chemokines that may crucially influence cell recruitment during an inflammatory challenge.…”
Section: Opn Mediates Macrophage Activationmentioning
confidence: 82%
See 3 more Smart Citations
“…4.3). It has been reported that OPN deficiency reduces the recruitment of macrophages, neutrophils and dendritic cells Koh et al, 2007;Weiss et al, 2001). These results imply that OPN allows the expression of chemokines that may crucially influence cell recruitment during an inflammatory challenge.…”
Section: Opn Mediates Macrophage Activationmentioning
confidence: 82%
“…Neutrophils (the majority of PMNs) are the primary responder to exogenous and endogenous stimuli and rapidly infiltrate the injured tissue to initiate an innate host defense. OPN is a chemoattractant for neutrophils (Weiss et al, 2001;Banerjee et al, 2006;Koh et al, 2007). Activated neutrophils release proteases and cytotoxic mediators in combination with phagocytosis and respiratory bursts to eliminate invading infectious agents.…”
Section: Neutrophilsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally CD44 ligation triggers neutrophil apoptosis in vitro [88]. Similarly Langerhans and dendritic cell migration is mediated at least in parts by CD44, since antibodies against CD44 block OPN-induced cell migration to lymphatic organs in mice [89]. Also the proliferation of mast cells is regulated by CD44 [90].…”
Section: Physiological Function In Cells Of Hematopoietic Originmentioning
confidence: 99%